Students’ Perceptions of the Journalists’ Questions Strategy in Enhancing EFL Writing Achievement - Zora, Zurina; Zulkifli, Zulkifli (Jurnal Ilmiah Guru Madrasah, 2025)
This study investigates students’ perceptions of the Journalists’ Questions strategy as a means of improving writing achievement in an English as a Foreign Language (EFL) context. While the strategy—built on the “five Ws and one H” framework—has been recognized for its potential to enhance idea generation and text organization, limited empirical evidence exists from Indonesian higher education settings, particularly in culturally distinctive regions such as Aceh. To address this gap, the study employed a qualitative-dominant mixed-methods design involving 17 undergraduate students from the Acehnese Language and Literature Education program at Universitas Islam Kebangsaan Indonesia. Data were collected through a closed-ended questionnaire and semi-structured interviews, then analyzed using descriptive statistics and thematic analysis. The results revealed consistently positive perceptions of the strategy across all measured aspects. The majority of students agreed or strongly agreed that Journalists’ Questions facilitated vocabulary selection, idea development, text organization, critical thinking, and grammatical accuracy. Interview data further illustrated that the strategy made writing tasks more engaging and less intimidating, while also enhancing motivation. Although initial challenges—such as limited vocabulary, sentence construction, and time management—were reported, these difficulties diminished with practice. The findings suggest that Journalists’ Questions is a practical, adaptable, and culturally relevant pre-writing strategy for EFL writing instruction in higher education. By providing structured guidance, it supports both the cognitive and affective dimensions of writing development. Implications for pedagogy include incorporating the strategy into writing curricula to improve learners’ confidence, coherence, and critical thinking skills.